IFPRI Policy Seminar Global Report on Food Crises 2021: Building resilience to prevent food crises and conflict - Boudreau, Tanya (2021)
Tanya Boudreau POLICY SEMINAR Global Report on Food Crises 2021: Building resilience to prevent food crises and conflict Co-Organized by IFPRI, FSIN, FAO North America, World Food Programme and the Food Security Portal JUN 17, 2021 - 09:30 AM TO 11:00 AM EDT